Profesionalisme Kinerja Guru dan Kemampuan Literasi Digital Guru Berpengaruh terhadap Kualitas Pembelajaran Daring SMK Kota Jambi - Elfa Suci Maharani; Rosmiati Rosmiati; Ahmad Nasori (Universitas Batanghari Jambi, 2021)
The purpose of this study is to determine whether there is an influence between: (1) the professionalism of teacher performance on the quality of online learning; (2) teachers' digital literacy skills on the quality of online learning; and (3) the professionalism of teacher performance and digital literacy skills of teachers on the quality of online learning. This research is a quantitative research using an Ex Po Facto research approach. The population in this study were 46 people. Sampling technique with saturated sample. The results showed that (1) there was an effect of X1 on Y with tcount > ttable (3.873 > 2.01669); (2) there is an effect of X2 on Y obtained tcount > ttable (2.480 > 2.01669); (3) there is a simultaneous effect, X1 and X2 on Y based on data analysis obtained Fcount > Ftable (16.506 > 3.214) and the coefficient of determination (R Square) is 0.434 which means that the quality of online learning is influenced by the professionalism of the teacher's performance and the teacher's digital literacy ability. by 43.4%. So it can be concluded that there is an influence of teacher performance professionalism and teacher digital literacy skills on the quality of online learning at SMK Negeri 5 Jambi City.